Postmodern society and its impact on the construction of identity and difference in Indonesia - Hulfadila, Hulfadila (Journal of Studies on Art, Culture and Society, 2024)
This article is about how postmodern society in Indonesia faces challenges and opportunities in creating its own identity and difference amid globalization and pluralism. The author uses sociological and anthropological approaches to analyze digital media, identity politics, ethnicity, religion, popular culture and social movements. The author shows that Indonesia's postmodern society seeks a flexible, dynamic and multicultural identity but simultaneously faces conflicts and tensions with different groups. The author also gives several recommendations to solve these problems and create social harmony.